TRNA evolution from the proto-tRNA minihelix world. Issue 5 (19th October 2016) - Root-Bernstein, Robert; Kim, Yunsoo; Sanjay, Adithya; Burton, Zachary F.
ABSTRACT: Multiple models have been advanced for the evolution of cloverleaf tRNA. Here, the conserved archaeal tRNA core (75-nt) is posited to have evolved from ligation of three proto-tRNA minihelices (31-nt) and two-symmetrical 9-nt deletions within joined acceptor stems (93 – 18 = 75-nt). The primary evidence for this conclusion is that the 5-nt stem 7-nt anticodon loop and the 5-nt stem 7-nt T loop are structurally homologous and related by coding sequence. We posit that the D loop was generated from a third minihelix (31-nt) in which the stem and loop became rearranged after 9-nt acceptor stem deletions and cloverleaf folding. The most 3´-5-nt segment of the D loop and the 5-nt V loop are apparent remnants of the joined acceptor stems (14 – 9 = 5-nt). Before refolding in the tRNA cloverleaf, we posit that the 3′-5-nt segment of the D loop and the 5-nt V loop were paired, and, in the tRNA cloverleaf, frequent pairing of positions 29 (D loop) and 47 (V loop) remains (numbered on a 75-nt tRNA cloverleaf core). Amazingly, after >3.5 billion years of evolutionary pressure on the tRNA cloverleaf structure, a model can be constructed that convincingly describes the genesis of 75/75-nt conserved archaeal tRNA core positions. Judging from the tRNA structure, cloverleaf tRNA appears to represent at least a second-generation scheme (and possibly a third-generation scheme) that replaced a robust 31-nt minihelix protein-coding system, evidence for which is preserved in the cloverleaf structure. Understanding tRNA evolution provides insights into ribosome and rRNA evolution.